MCPBA-Promoted Tandem Michael Addition–Intramolecular Cyclization of 2-Azido-β-amino Esters: Single Pot, Convenient Access to 1,2,4,5-Tetrasubstituted Imidazoles - Raj, Raghu; Hundal, M. S.; Kumar, Vipan (Synlett, 2014)
A simple, single-pot synthesis of tetrasubstituted imidazoles has been developed through the use of MCPBA-promoted tandem Michael addition–intramolecular cyclization of 2-azido-β-amino esters.
Keywords: multicomponent reactions; small ring systems; Michael addition; intramolecular cyclization; imidazoles